FREQUENCY OF FORMATION OF VAPOR BUBBLES IN A TWO-LAYER MEDIUM MAGNETIC-NONMAGNETIC LIQUID - Alexander Aleksandrovich Yanovsky; Alexander Yakovlevich Simonovsky (Наука. Инновации. Технологии)
Introduction: a method for measuring the frequency of the formation of vapor bubbles in the boiling of opaque fluids using a two-layer system is proposed and implemented: an opaque - transparent medium. An experimental setup has been developed and experiments have been carried out to determine the frequency of the formation of vapor bubbles during the boiling of opaque liquids. Materials and methods: A method for measuring the frequency of formation of vapor bubbles in the boiling of opaque liquids by means of a two-layer system is proposed and implemented: an opaque - transparent medium. An experimental setup has been developed and experiments have been carried out to determine the frequency of the formation of vapor bubbles during the boiling of opaque liquids. The results of the study: The frequency of formation of vapor bubbles was measured in the boiling of a two-layer medium by a non-magnetic liquid on an unrestricted horizontal surface with pointwise heat input in a uniform external magnetic field. It is found that with the increase in the strength of a uniform constant magnetic field, the frequency of the formation of vapor bubbles upon boiling of a two-layer medium of a magnetic-nonmagnetic liquid on an unbounded horizontal plate decreases, and the temperature of the heat-releasing surface at which the vaporization process begins increases for samples of magnetic liquids with a high magnetic phase content. Discussion and conclusions: The dependence of the frequency of the formation of vapor bubbles on the temperature of the heat-releasing surface is found experimentally at the boiling of a magnetic fluid in various magnetic fields with different intensities and directions. It is found that with the increase in the strength of a uniform constant magnetic field, the frequency of the formation of vapor bubbles upon boiling of a two-layer medium of a magnetic-non-magnetic liquid on an unbounded horizontal plate decreases, and the temperature of the heat-releasing surface at which the vaporization process begins increases for samples of magnetic liquids with a high magnetic phase content.